Speech by the Chairperson of the University of Embu Council Dr. Margaret Gikuhi on the occasion of Launch of the University of Embu Endowment Fund to be Held at the University of Embu on Thursday, 25th October 2018. - Gikuhi, Margaret (University of Embu, 2018)
Speech by the Chairperson of the University of Embu Council Dr. Margaret Gikuhi on the occasion of Launch of the University of Embu Endowment Fund to be Held at the University of Embu on Thursday, 25th October 2018.